PENINGKATAN DAYA RETENSI SISWA MELALUI LESSON STUDY DENGAN PBL (PROBLEM BASED LEARNING) PADA MATERI LINGKARAN - Naning Kurniawati (Journal of Mathematics Education and Science, 2018)
Lesson study (LS) is a continuous assessment activity conducted by a group of teachers / lecturers on a regular and continuous basis to test and improve the effectiveness of learning. Lesson study through planning activities, implementation (do) and reflection (see) collaboratively which aims to improve the quality of learning. Lesson Study conducted can encourage students to learn actively, creatively, precisely and fun. Lesson Study can also improve the observation capabilities in the classroom so that teachers can pay attention to the students one by one. Lesson study activities conducted at SMPN 1 Baureno aims to improve teacher competence and improve the quality of learning in the classroom. At the time of open class, learning is done by approach of PBL (Problem Based Learning) which is equipped with worksheet. The PBL (Problem Based Learning) approach or problem based learning is chosen because it can improve students retention by finding principles and formulas. According to the observer, open class activities with group discussion methods can improve students' understanding and retention of the material so that students remember longer material and can apply the formula appropriately. With Lesson Study more enjoyable learning so that students are more enthusiastic in following learning. Lesson study (LS) yaitu kegiatan pengkajian berkelanjutan yang dilakukan sekelompok guru/dosen secara berkala dan berkelanjutan untuk menguji dan meningkatkan keefektifan pembelajaran. Lesson study melalui kegiatan perencanaan (plan), pelaksanaan (do) dan refleksi (see) secara kolaboratif yang bertujuan untuk memperbaiki kualitas pembelajaran. Lesson Study yang dilakukan dapat mendorong siswa belajar dengan aktif, kreatif, tepat dan menyenangkan. Lesson Study juga dapat meningkatkan kemampuan observasi di kelas sehingga guru dapat memperhatikan siswa satu persatu. Kegiatan lesson study yang dilaksanakan di SMPN 1 Baureno bertujuan untuk meningkatkan kompetensi guru dan meningkatkan mutu pembelajaran di kelas. Pada saat open class, pembelajaran dilaksanakan dengan pendekatan PBL (Problem Based Learning) atau pembelajaran berbasis masalah yang dilengkapi dengan lembar kerja. Pendekatan PBL (Problem Based Learning) atau pembelajaran berbasis masalah dipilih karena dapat meningkatkan daya retensi siswa dengan menemukan prinsip dan rumus. Menurut observer, kegiatan open class dengan metode diskusi kelompok dapat meningkatkan pemahaman dan daya retensi siswa terhadap materi sehingga siswa lebih lama mengingat materi dan dapat mengaplikasikan rumus dengan tepat. Dengan Lesson Study pembelajaran lebih menyenangkan sehingga siswa lebih antusias dalam mengikuti pembelajaran.